Controllable synthesis of porous tubular carbon by a Ag+-ligand-assisted Stöber-silica/carbon assembly process. Issue 4 (21st January 2021) - Shen, Yang-Lin; Jin, Jun-Ling; Chen, Ning; Li, Peng Ju; Xu, Ting; Xie, Yun-Peng; Lu, Xing
Abstract : Porous carbon tubes have been produced for the first time via a Stöber-silica/carbon co-assembly process upon dictation by Ag + and pyridyl-functionalized surfactants. Abstract : Herein, in this study, we utilized Ag + -ligand interactions for critically regulating the morphology of carbon by the Stöber-silica/carbon co-assembly method for the first time. Tetraethyl orthosilicate (TEOS) and resorcinol/formaldehyde (RF) assemble upon dictation by Ag + and pyridyl-functionalized surfactants, producing porous carbon tubes (RF1 ) with a high surface area of 696 m 2 g −1 and accessible mesopores ∼15 nm in size. Furthermore, when using tetrapropyl orthosilicate (TPOS) with a slower hydrolysis rate than that of TEOS, carbon tubes (RF2 ) with enhanced uniformity and a surface area as high as 2112 m 2 g −1 are generated. Additionally, when using dopamine hydrochloride instead of RF as a carbon precursor, tubular polydopamine (TDA ) with lengths of tens of microns is fabricated, which exhibits excellent catalytic activity toward oxygen reduction reactions in alkaline solutions due to its unique structural feature, a high surface area of 1350 m 2 g −1, metallic silver remains of 8.3 wt%, and a rich nitrogen content of 3.6 wt%. This work sheds light on the engineering of a micellar soft template and synthesizing novel nanostructures by the extension of the Stöber method.